2023
DOI: 10.1021/acs.est.3c00226
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effect of Hg(II) Speciation, Thiol Metabolism, and Cell Physiology on Methylmercury Formation by Geobacter sulfurreducens

Abstract: The chemical and biological factors controlling microbial formation of methylmercury (MeHg) are widely studied separately, but the combined effects of these factors are largely unknown. We examined how the chemical speciation of divalent, inorganic mercury (Hg(II)), as controlled by low-molecular-mass thiols, and cell physiology govern MeHg formation by Geobacter sulfurreducens . We compared MeHg formation with and without addition of exogenous cysteine (Cys) to experimental assays with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…We hypothesize that Cys acts as a carrier to facilitate MeHg transportation in rice plants, as observed in chlorophytes and microorganisms. , The presence of Cys promotes the formation of the Hg–Cysteine complex, which can be actively taken up by Geobacter sulfurreducens via the plasma membrane transporters . The chemical structures of the MeHg–Cysteine complex depend on the reaction between Cys and MeHg, particularly on the molecular ratio of MeHg to Cys.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We hypothesize that Cys acts as a carrier to facilitate MeHg transportation in rice plants, as observed in chlorophytes and microorganisms. , The presence of Cys promotes the formation of the Hg–Cysteine complex, which can be actively taken up by Geobacter sulfurreducens via the plasma membrane transporters . The chemical structures of the MeHg–Cysteine complex depend on the reaction between Cys and MeHg, particularly on the molecular ratio of MeHg to Cys.…”
Section: Resultsmentioning
confidence: 96%
“…71,72 The presence of Cys promotes the formation of the Hg−Cysteine complex, which can be actively taken up by Geobacter sulfurreducens via the plasma membrane transporters. 73 The chemical structures of the MeHg−Cysteine complex depend on the reaction between Cys and MeHg, particularly on the molecular ratio of MeHg to Cys. The variety of chemical structures of MeHg−Cysteine complex affects their bioavailability and accumulation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Thus, from FTIR, EDX, and XPS analysis results, we can conclude that the biosyntheses of CdSe core and CdSe@ZnSe core–shell QDs using HSA form a layer on the respective QDs surface, having both functional groups (positive and negatively charged ) intake with the protein layer. The passivating layer (especially the -SH group) provides a robust biochemical affinity toward Hg 2+ . The excellent luminescence properties and the strong affinity toward Hg 2+ of the respective biosynthesized QDs lay the basis for a fluorescence probe for Hg 2+ ions.…”
Section: Resultsmentioning
confidence: 99%
“…The passivating layer (especially the -SH group) provides a robust biochemical affinity toward Hg 2+ . 63 The excellent luminescence properties and the strong affinity toward Hg 2+ of the respective biosynthesized QDs lay the basis for a fluorescence probe for Hg 2+ ions. Moreover, the extremely small size (TEM and XRD analyses) of the synthesized respective CdSe-HSA and CdSe@ ZnSe-HSA QDs and their unique surface properties also open a new window to treating the synthesized bio-QDs as antimicrobial agents.…”
mentioning
confidence: 99%
“…A possible role of glycogen as a long-term electron storage in electroactive G. sulfurreducens biofilms has been addressed [ 60 ]. The evidence of glycogen accumulation in G. sulfurreducens obtained using ATR-FTIR spectroscopy has recently been reported [ 61 ]. It was found that upon the transfer of planktonic cells into a minimal nutritive medium used for Hg(II) methylation assays the content of glycogen in bacteria varies as a function of time.…”
Section: Discussionmentioning
confidence: 99%